SOUTHEAST ASIA BUSINESS GROWTH STRATEGY OF GREEN ADDITIVE IN DECORATIVE PAINT MARKET AT ROXY CHEM COMPANY - Purnomo, Rosiana Irta; Anggoro, Yudo (CV. Radja Publika, 2025)
Roxy Chem is a global material science company based in the United States with a diverse product portfolio in the coating market. The global paint market is projected to grow, and Southeast Asia is identified as a key region for growth due to rapid industrialization and urbanization, with an estimated CAGR around 5-7%. The decorative paint market holds the largest share in the global coating market. Aligning with its sustainability goals, Roxy Chem focuses on the decorative paint market, and Southeast Asia is considered as an important region for Roxy Chem’s strategy to increase its market shares. In Southeast Asia, Roxy Chem encounters several challenges and issues in expanding its market shares. Primarily, due to the lack of stringent air pollution regulations, aggressive competition and long lead times for product delivery. With the pressure from the CEO and a top-down strategy to grow the market shares, it is necessary to define a comprehensive participation strategy that will enable the company to increase the market share from 5% to 30% by the year of 2030. Formulating an effective strategy to increase market share is crucial for enhancing the success rate following data collection through in-depth interviews for key end users and distributors across Southeast Asia. Initially, understanding internal and external factors that affect decorative paint market in SEA is necessary to identify the opportunities and challenges to grow the market. Once the factors are understood, Roxy Chem can develop their strategy utilizing STP (Segmentation, Targeting, Positioning) framework and the marketing mix 4Ps. Finally, based on the strategies developed, Roxy Chem can outline an implementation plan and conduct opportunity review using the Real, Win, Worth (RWW) framework to surpass the competitors in the market. By executing the participation strategy, Roxy Chem can achieve its growth objectives and improve its profitability in the long run.